2017
DOI: 10.13189/ujer.2017.050312
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teacher Training on the Learning Styles of Prospective Teachers of Social Studies

Abstract: The purpose of this study is to examine the effects of four-year-long undergraduate education on the learning styles of prospective teachers of social studies. This study was conducted in accordance with longitudinal method, which is one of the research designs used in developmental psychology researches. The study was conducted with the participation of 70 prospective teachers of social studies who studied at Ondokuz Mayis University Faculty of Education between 2009 and 2013 and who volunteered to participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Both this study and other studies conducted on the learning styles of the prospective teachers in Turkey indicate that dominant learning style of the majority of the prospective teachers is the assimilating learning style. And in the dimensional study performed by Ozdemir et al [75] on the prospective social sciences teachers, it was found that undergraduate education did not cause a significant difference in the perception (concrete experience-abstract conceptualization) and processing (reflective observation-active experimentation) ways in the learning styles of prospective teachers and similar results were found when the variable of gender was taken as the basis. However, the researches performed abroad on this subject suggest that the dominant learning style of the ones involved in the profession of teaching is the accommodating learning style [35,76,77].…”
Section: Discussion and Resultsmentioning
confidence: 62%
“…Both this study and other studies conducted on the learning styles of the prospective teachers in Turkey indicate that dominant learning style of the majority of the prospective teachers is the assimilating learning style. And in the dimensional study performed by Ozdemir et al [75] on the prospective social sciences teachers, it was found that undergraduate education did not cause a significant difference in the perception (concrete experience-abstract conceptualization) and processing (reflective observation-active experimentation) ways in the learning styles of prospective teachers and similar results were found when the variable of gender was taken as the basis. However, the researches performed abroad on this subject suggest that the dominant learning style of the ones involved in the profession of teaching is the accommodating learning style [35,76,77].…”
Section: Discussion and Resultsmentioning
confidence: 62%
“…The fact that prospective teachers preparing for Public Personnel Selection Examination (KPSS) mostly study on their own, the recognition of the need for being more patient and careful in learning process, experiencing a difficult studying period due to knowing that they can become a teacher only after passing a three-stage exam, and the possibility that this process may cause prospective teachers adopt a more sensory approach may have an impact on the learning styles of the participants. Indeed, it is well-known that individuals with "diverging" learning style are inclined to become emotional, prefer individual studying when learning, and become patient and careful in learning process [22,23].…”
Section: Resultsmentioning
confidence: 99%